Agronomic performance of amaranth under planting arrangements and the effect of the environment on its emergence and early growth - Gomes, Victor Emmanuel de Vasconcelos (2023)
Amaranth is a grain that has gained prominence because it is well adapted to adverse climate and soil conditions, in addition to having significant potential to be better exploited for both human and animal consumption. Two experiments were carried out: a field experiment aimed at evaluating how cropping arrangements and planting densities affect the agronomic performance of amaranth plants; and an experiment under controlled environment conditions (greenhouse) aiming to evaluate how sowing depth and soil types affect emergence and initial growth of two amaranth cultivars. To achieve the first objective, an experiment was conducted in a randomized block design, in which five planting densities (62,500; 83,333; 111,111; 125,000 and 166,666 plants ha-1) were tested, in two cultivation cycles (2019 and 2020), in the municipality of Pentecoste-CE. To achieve the second objective, an experiment was carried out evaluating the emergence and initial growth of two amaranth cultivars (A. cruentus BRS Alegria and A. caudatus Inca) submitted to three types of soil (loam, clayey loam and clayey) and five soil depths. seeding (0; 5; 10; 15 and 20 mm) in a randomized block design in a 2x3x5 factorial scheme. The experiment was conducted in two immediately subsequent evaluation periods. Planting densities had little effect on plant growth, affecting only stem diameter and plant tipping over, with a density of 83,333 pl ha-1 favoring a greater stem diameter, while a density of 62,500 pl ha-1 favoring a smaller plant tipping index. Higher density resulted in higher fresh and dry matter yield, grain yield and harvest index. The weight of a thousand grains was higher in the density 83,333 pl ha-1. The 30 x 20 cm spatial arrangement with 166,666 pl ha-1 can be recommended for the cultivation of amaranth in the study area. Regarding the greenhouse experiment, it was observed that the soil type, sowing depth and cultivar had a significant effect on emergence and initial growth of amaranth. A. caudatus showed the highest seedling height, stem diameter, number of leaves, root length, and fresh and dry weights. Seedling emergence was affected by the cultivar and was 15% higher for the A. cruentus cultivar. Plant height was greatest when plants were sown at a depth between 5 and 20 mm. Root length varied as a function of the interaction between soil types and sowing depth, with the longest root length being obtained when amaranth was sown in loam or clayey soil at a depth of 10 mm.